Sequence Stratigraphic and Geochemical Records of Paleo-Sea Level Changes in Upper Carboniferous Mixed Clastic–Carbonate Successions in the Eastern Qaidam Basin - Yifan Li; Xiaojie Wei; Kui Liu; Kening Qi (Journal of Marine Science and Engineering)
The Upper Carboniferous strata in the eastern Qaidam Basin, comprising several hundred meters of thick, mixed clastic–carbonate successions that have been little reported or explained, provide an excellent geological record of paleoenvironmental and paleo-sea level changes during the Late Carboniferous icehouse period. This tropical carbonate–clastic system offers critical constraints for correlating equatorial sea level responses with high-latitude glacial cycles during the Late Paleozoic Ice Age. Based on detailed outcrop observations and interpretations, five facies assemblages, including fluvial channel, tide-dominated estuary, wave-dominated shoreface, tide-influenced delta, and carbonate-dominated marine, have been identified and organized into cyclical stacking patterns. Correspondingly, four third-order sequences were recognized, each composed of lowstand, transgressive, and highstand system tracts (LST, TST, and HST). LST is generally dominated by fluvial channels as a result of river juvenation when the sea level falls. The TST is characterized by tide-dominated estuaries, followed by retrogradational, carbonated-dominated marine deposits formed during a period of sea level rise. The HST is dominated by aggradational marine deposits, wave-dominated shoreface environments, or tide-influenced deltas, caused by subsequent sea level falls and increased debris supply. The sequence stratigraphic evolution and geochemical records, based on carbon and oxygen isotopes and trace elements, suggest that during the Late Carboniferous period, the eastern Qaidam Basin experienced at least four significant sea level fluctuation events, and an overall long-term sea level rise. These were primarily driven by the Gondwana glacio-eustasy and regionally ascribed to the Paleo-Tethys Ocean expansion induced by the late Hercynian movement. Assessing the history of glacio-eustasy-driven sea level changes in the eastern Qaidam Basin is useful for predicting the distribution and evolution of mixed cyclic succession in and around the Tibetan Plateau.